Exploring International Partnership for Sustainability of International Academic Program and Global Achievement: A Case Study - Widarwati, Estu; Tahir, Egi Milmayadi; Kurniawan, Asep; Apriandi, Devi Widya; Susandy, Gugyh; Nurmalasari, Nunik; Umiyati, Indah; Wityasminingsih, E. (KnE Social Sciences, 2025)
The global achievements of sustainability using the exploration of cooperation networks in higher education are very important for a competitive advantage. Designing international academic programs with global partners leads to the guarantee of student learning and their interaction with international parties of campuses, institutions, and industries. The various types of international academic programs are needed for university excellence, additionally, international cooperation partners can maintain their existence by collaborating in the program design which further provides benefits for both parties such as the creation of positive branding, increasing trust, and human resources quality for cooperation sustainable of both parties in the long term. This paper discusses the international academic program between Sekolah Tinggi Ilmu Ekonomi Sutaatmadja Subang (STIESA) and its international partnerships during 2019-2024. We use an explanatory method that explores STIESA’s International Partnerships in relation to both the international academic programs and global achievements. Then, we also used the survey method including three respondents’ perspectives STIESA’s cooperation partner, and students to complete our analysis. The regression panel approach and robustness check are used for examining the relation of variables. The results show a significant relationship between STIESA’s International Partnerships both on the sustainability of the International Academic Program and global achievements. These findings imply that a university needs to increase international partnerships and/or participate in international academic programs involving international partners to maintain the sustainability of international achievements and global competitiveness.